Power talk : insights from Asia's leading entrepreneurs - Lam, Karen (New Jersey : World Scientific, 2018)
'What drives success in Asia? How did the pioneers do what they did, how are they planning their succession? After six seasons of Channel NewsAsia's Power List Asia, with 73 high-powered guests, over 26,000 manhours of pre- and post-production and 130,000 airmiles, comes Power Talk. Distilling the very best and most memorable conversations with various head honchos, Karen Lam sits down (not on television this time) to compile the best business ideas, personal philosophies, attitudes and intriguing stories into common themes of leadership and entrepreneurship in Asia. Featuring more than 20 Powerlisters and a range of topics such as crisis management, brand building, expanding westward and succession planning, Power Talk is a must-read for any Asian entrepreneur on the cusp of that next league'--
Includes bibliographical references and index.
Keywords: Executive ability -- Asia; Chief executive officers -- Asia; Success in business -- Asia; Entrepreneurship -- Asia; Business enterprises -- Asia